Peran Gembala Terhadap Manajemen Pola Pemuridan Kristen dalam 2 Timotius 2:2 di Era Disrupsi - Purba, Jhon Leonardo Presley; Saptorini, Sari (Sekolah Tinggi Agama Kristen Diaspora Wamena, 2021)
Advances in technological innovation and various changes that occur cause an era of disruption that cannot be avoided. This disruption needs to be addressed in an adaptive manner so that it can be utilized for the advancement of Christian discipleship ministry as the pattern in 2 Timothy 2:2. The role of the Shepherd is very significant here, which requires good management skills. Using a descriptive qualitative approach with literature study and hermeneutic-exegesis methods, this paper aims to answer the research question, namely what and how is the role of the shepherd in the management of Christian discipleship patterns in 2 Timothy 2:2 in the era of disruption. This study concludes that a shepherd must play a role and function as a catalyst in discipleship services, which also has implications for the need for humanistic integrity to utilize technology-digitalization in the era of disruption for discipleship services through a benefit principle approach in order to be able to face and adapt to the era of disruption. As a catalyst, the shepherd plays a role in selecting and involving faithful believers, as well as the Church as an organization in the ministry of discipleship. the shepherd plays a role in managing discipleship services like the pattern in 2 Timothy 2:2 well through systematic efforts in planning, organizing, directing, coordinating, and controlling or systematically planning, implementing, controlling, and following up by analyzing the composition of skills , the strengths and personality of each member of the service team, conduct periodic evaluations individually and in teams, and perform synergies between human resources and non-human resources as ministry support so that the vision and goals of Christian discipleship are in the Great Commission of the Lord Jesus (Matt. 28:18-20) can be achieved.AbstrakKemajuan inovasi teknologi dan berbagai perubahan yang terjadi menyebabkan terjadinya era disrupsi yang tidak dapat dihindari. Disrupsi ini perlu disikapi dengan adaptif agar dapat dimanfaatkan untuk kemajuan pelayanan pemuridan Kristen seperti pola dalam 2 Timotius 2:2. Peran gembala sangat signifikan disini, yang menuntut kemampuan manajemen yang baik. Menggunakan pendekatan kualitatif deskriptif dengan metode studi literature dan hermeneutik-eksegesis, paper ini bertujuan menjawab pertanyaan penelitian yaitu apa dan bagaimana peran gembala terhadap manajemen pola pemuridan Kristen dalam 2 Timotius 2:2 di era disrupsi. Kajian ini menyimpulkan bahwa seorang gembala harus berperan dan berfungsi sebagai katalisator dalam pelayanan pemuridan, yang juga berimplikasi pada dibutuhkannya integritas yang humanistik untuk memanfaatkan teknologi-digitalisasi di era disrupsi bagi pelayanan pemuridan melalui pendekatan azas manfaat agar mampu menghadapi dan beradaptasi dengan era disrupsi. Sebagai katalisator, gembala berperan memilih dan melibatkan orang-orang percaya yang setia, juga Gereja sebagai organisasi dalam pelayanan pemuridan. gembala berperan melakukan manajemen pelayanan pemuridan seperti pola dalam 2 Timotius 2:2 dengan baik melalui upaya yang sistematis dalam membuat perencanaan, pengorganisasian, pengarahan, pengkoordinasian, dan pengendalian atau secara sistematis membuat perencanaan, pelaksanaan, kontrol, dan tindak lanjut dengan melakukan analisis komposisi skill, kelebihan dan kepribadian masing-masing anggota tim pelayanan, melakukan evaluasi berkala secara individu dan tim, dan melakukan integrasi-sinergitas antara sumber daya manusia dan sumber daya non manusia sebagai penunjang pelayanan agar visi dan tujuan pemuridan Kristen dalam Amanat Agung Tuhan Yesus (Mat. 28:18-20) dapat tercapai.